Sea Level Rise and the Dynamics of the Marsh-Upland Boundary - Fagherazzi, Sergio; Anisfeld, Shimon C.; Blum, Linda K.; Long, Emily V.; Feagin, Rusty A.; Fernandes, Arnold; Kearney, William S.; Williams, Kimberlyn (Frontiers in Environmental Science, 2019)
During sea level rise, salt marshes transgress inland invading low-lying forests, agricultural fields, and suburban areas. This transgression is a complex process regulated by infrequent storms that flood upland ecosystems increasing soil salinity. As a result upland vegetation is replaced by halophyte marsh plants. Here we present a review of the main processes and feedbacks regulating the transition from upland ecosystems to salt marshes. The goal is to provide a process-based framework that enables the development of quantitative models for the dynamics of the marsh-upland boundary. Particular emphasis is given to the concept of ecological ratchet, combining the press disturbance of sea level rise with the pulse disturbance of storms.